Can low-carbon urban development be pro-poor? The case of Kolkata, India. (April 2017) - Colenbrander, Sarah; Gouldson, Andy; Roy, Joyashree; Kerr, Niall; Sarkar, Sayantan; Hall, Stephen; Sudmant, Andrew; Ghatak, Amrita; Chakravarty, Debalina; Ganguly, Diya; Mcanulla, Faye
Fast-growing cities in the global South have an important role to play in climate change mitigation. However, city governments typically focus on more pressing socioeconomic needs, such as reducing urban poverty. To what extent can social, economic and climate objectives be aligned? Focusing on Kolkata in India, we consider the economic case for low-carbon urban development, and assess whether this pathway could support wider social goals. We find that Kolkata could reduce its energy bill by 8.5 per cent and greenhouse gas emissions by 20.7 per cent in 2025, relative to business-as-usual trends, by exploiting readily available, economically attractive mitigation options. Some of these measures offer significant social benefits, particularly in terms of public health; others jeopardize low-income urban residents' livelihoods, housing and access to affordable services. Our findings demonstrate that municipal mitigation strategies need to be designed and delivered in collaboration with affected communities in order to minimize social costs and – possibly – achieve transformative change.